Penerapan Metode Kano, Customer Satisfaction Index dan Quality Function Deployment dalam Menganalisis Kepuasan Mahasiswa Terhadap Penerapan MB-KM - Usman, Sri Adiningsi B.; Isa, Dewi Rahmawaty; Nuha, Agusyarif Rezka (ESTIMASI: Journal of Statistics and Its Application, 2024)
The implementation of the MB-KM program in Higher Education has a variety of obstacles based on points of view. Internship is a form of implementing the MB-KM program which involves students as executors of the program. This study aims to analyze student satisfaction with the implementation of MB-KM using the Kano method, Customer Satisfaction Index (CSI) and Quality Function Deployment (QFD). The Kano method aims to categorize variable attributes, the CSI method to calculate the overall level of satisfaction and the QFD to determine priority attribute improvements. Kano's results show that 5 attributes are in quadrant A, 30 attributes are in quadrant O, 5 attributes are in quadrant I and 13 attributes are in quadrant M. The results of the analysis of the Customer Satisfaction Index are 87.57% meaning students are "very satisfied". The final result of the HOQ attribute that is the priority is attribute .